SOSIALISASI PENINGKATAN KETERLIBATAN PEMILIH PEMULA PADA PEMILU 2024 DI KECAMATAN SARJO - Mangngasing, Nasir; Haryono, Dandan; Nuraisyah, Nuraisyah; Nasrullah, Nasrullah; Indriani, Niluh (Publikasi Ilmiah Bidang Pengabdian Kepada Masyarakat (SIKEMAS), 2023)
Socialization of Increasing Beginner Voter Involvement in the 2024 Election in Sarjo District is a very important thing where the involvement of first-time voters in 2024 is very substantive and a very good support for the success of the upcoming general elections which will give birth to leaders who come from party results bureaucracy, be it presidential election or election for members of DPRRI, DPDRI, Provincial DPRD and Regency/City DPRD. The purpose of carrying out this activity is to find out the strategy that must be carried out in maximizing first-time voters, then the Beginner Voter Management Strategy which is dominated by Generation Z. The targeted outputs of this service are: first, strengthening the understanding of first-time voters through the results of outreach; second, Journal Publication in national service journals; and third, HKI is made to support the University's IKU. The result of this dedication and research is that Beginner Voter Socialization and Education has not been carried out intensively and education about the importance of political participation, rights and responsibilities as citizens, and the election process. Beginner voters must be given a comprehensive understanding of the political system and the impact of their active participation in selecting representatives.